The Causal Impact of Counsel at First Appearance: Evidence from Two Randomized Control Trials - George S Naufal; Bethany Patterson; Renee Danser; D. James Greiner (Institute of Labor Economics (IZA), 2025)
This paper examines the impact of defense counsel at first appearance (CAFA) on criminal justice outcomes using randomized control trials in two Texas counties. The study evaluates the influence of CAFA on bond amounts, pretrial release, conditions, and post-magistration outcomes such as recidivism and failure to appear. Results show that while CAFA reduces bond amounts and influences bond types in one jurisdiction, its effects on pretrial release and recidivism are limited. These findings highlight jurisdictional differences and suggest that CAFA's impact may be more modest than previous studies indicate, underscoring the need for further research in this area.
Keywords: C93; J08; K4; K14; 330; first appearance; RCT; bail; pretrial release